ISOLASI cDNA SUCROSE TRANSPORTER (SUT) DARI BATANG TANAMAN TEBU (Saccharum officinarum L.) - - Slameto; Bambang Sugiharto (Universitas Trunojoyo Madura, 2010)
Sucrose Transporter (SUT) is kind of protein transporter that control in sucrose translocation. Sucrose Transporter is intermediate in translocation of sucrose from apoplasmic to simplasmic. SUT facilitates sucrose transportation from vascular tissues to parenchyma cells toward in node sugarcane stem. This research was purposed to isolate cDNA SUT from sugarcane stem, and cloned in Escherichia coli strain DH5α. Total RNA of sugarcane stem was isolated by single step method, then add with oligo dT in order to obtain the first strand of SUT cDNA then used as template for PCR. The primer used for PCR is 5’ –ggg ctg att gtg gcc atg tc- ‘3 (SUT-F) and 5’ –tgc cct ttg tct ccg gaa cc- ‘3 (SUT-R). PCR was programmed as follow denaturation at 94°C for 2 minutes and 30 second, annealing at 54°C for 30 s, extension at 72°C 2 min and 7 min, and storage at 4°C for unlimited, It was for 30 cycles. Complementary DNA SUT from PCR ligalized to pTOPO bunt-end, then it cloned in to E. coli strain DH5α. The cloning resulted then be sequenced in order to observe the homologues with other nucleotides sequences of some plant using BLASTn program in GENE BANK NCBI and the level of homology determined by Genetyx program. The concentrated of total RNA isolated was 5,024 μg/μl, with purity of 1,85. Complementary DNA SUT fragment from PCR with size 2037 bp appropriated to the both of primer was used. Complementary DNA SUT fragment showed by analyzed some of restriction enzyme e.g. EcoRI, PstI and BamHI. Homologues of this cDNA SUT fragment was 100% to SoSUT 2A of sugarcane stem and 84% to OsSUT of rice plant (Casu et al ., 2003).